2023
DOI: 10.1097/prs.0000000000010682
|View full text |Cite
|
Sign up to set email alerts
|

Does Revision Carpal Tunnel Release Result in Long-term Outcomes Equivalent to Single Carpal Tunnel Release? A Matched Case-Control Analysis.

Abstract: In the United States, approximately 600,000 patients undergo carpal tunnel release (CTR) annually for carpal tunnel syndrome (CTS). 1 CTR is an effective treatment to improve grip strength and decrease paresthesia in patients with CTS. 2,3 However, in up to 30% of patients, residual symptoms persist or recur, leading to revision surgery in up to 5%. [4][5][6][7][8][9][10][11] Although most studies suggest that the outcome after revision surgery is worse compared with single, initial CTR, some studies report ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In our cohort, symptom recurrence was the most common indication for revision CTR (59% of revisions) followed by symptom persistence (40% of revisions). Although prior studies have reported symptom persistence as the most common indication, 5,6,8,11,15 they were based on smaller cohorts with shorter follow-up, supporting the call for longer-term studies. 22 We found that revision for recurrent symptoms occurred at a significantly longer median interval of 4.1 years, compared with 1.2 years for persistent symptoms, and our data indicate that reoperation for recurrence of symptoms was more common than previously recognized.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In our cohort, symptom recurrence was the most common indication for revision CTR (59% of revisions) followed by symptom persistence (40% of revisions). Although prior studies have reported symptom persistence as the most common indication, 5,6,8,11,15 they were based on smaller cohorts with shorter follow-up, supporting the call for longer-term studies. 22 We found that revision for recurrent symptoms occurred at a significantly longer median interval of 4.1 years, compared with 1.2 years for persistent symptoms, and our data indicate that reoperation for recurrence of symptoms was more common than previously recognized.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, we report the largest study on this topic to date, providing important information to help guide surgeons and patients in their selection of CTR technique. Although revision CTR is uncommon, delineating its incidence and risk factors is important for public health, considering that CTR is among the most common operations in the US and that outcomes of revision CTR are suboptimal . With recent studies reporting an increased risk of revision CTR following ECTR, precise characterization of this association is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If symptoms persist despite conservative treatment, reoperation may be indicated. Although improved symptoms are reported, outcomes after revision surgery are generally worse than primary surgery (Westenberg et al, 2023). Moreover, unlike primary CTR, revision surgery is much more complex due to scarring and unpredictable in terms of anatomical findings (Figure 5).…”
Section: Failure Of Treatmentmentioning
confidence: 99%